EVALUATION OF ANALGESIC ACTIVITY OF ETHANOLIC EXTRACT OF CANANGA ODORATA LAM IN EXPERIMENTAL ANIMALS - YASMEEN A MANIYAR; JANAKI DEVI C.H. (International Journal of Pharma and Bio Sciences, 2015)
The present study evaluates the central and peripheral analgesic activity of ethanolic extract of Cananga Odorata Lam [EECO] in experimental animals.Acute toxicity test was done following OECD guidelines. EECO (100mg/kg, 200mg/kg and 400mg/kg b.w. p.o) was evaluated for central and peripheral analgesic activity by the Tail flick method in wistar rats and 0.7%acetic acid induced Writhing test in Swiss albino mice respectively. Aspirin was used as the standard drug in the dose of 300 mg/kg b.w. in tail flick method and 100 mg/kg b.w. in acetic acid induced writhing test. EECO significantly increased the reaction time in tailflick method(p<0.01) at all the doses and decreased the number of writings in Writhing test (p<0.01) at all the doses.EECO has significant central and peripheral analgesic activity.